1974
DOI: 10.1111/j.1365-2338.1974.tb02388.x
|View full text |Cite
|
Sign up to set email alerts
|

RESUME:Studies on the Chemical Control of Aonidiella aurantii (Mask.)

Abstract: Aonidiella aurantii (Mask.) which was accidentally introduced in Sicily in 1968 has since become a dangerous pest requesting special treatments in citrus groves. Experiments have been carried out on Citrus lemon to evaluate the efficacy of several organophosphorous compounds partly in mixture with white oil and this latter applied sole (cf. table 1). The results obtained against young females are set out in table 2; they show excellent results with almost all compounds whereas the same pesticides had a rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(1997), Phillips et al (1983), Uygun and Sekeroglu (1984), Zuniga (1985), Morse and Bellows (1986), Grafton-Cardwell and Reagan (1995), Rajagopal (1995 and1998), Liotta and Mineo (2008) and Reecha, et al (2009). The present paper describes some laboratory and field tests on the effect of KZ oil, Neemex, Sulphur and Actalic compounds on A. aurantii and its parasitoid, C. lemniscata.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1997), Phillips et al (1983), Uygun and Sekeroglu (1984), Zuniga (1985), Morse and Bellows (1986), Grafton-Cardwell and Reagan (1995), Rajagopal (1995 and1998), Liotta and Mineo (2008) and Reecha, et al (2009). The present paper describes some laboratory and field tests on the effect of KZ oil, Neemex, Sulphur and Actalic compounds on A. aurantii and its parasitoid, C. lemniscata.…”
Section: Introductionmentioning
confidence: 99%
“…In Swaziland, when dangerous populations of A. aurantii developed in midsummer (when natural enemies were least effective), a mixture of parathion and dimethoate, or summer oil emulsion, was applied in February-March(Catling,1971) Nigam (1971). stated that A. aurantii attacks mulberry in the Darjeeling district of West Bengal (India) and controlled chemically by 0.05% parathion (Folidol) Liotta and Mineo (2008). concluded that the replacement of white oils by organophosphorous compounds is not justified providing that the control is directed against larvae and young females of A. aurantii In Italy.…”
mentioning
confidence: 99%